2023
DOI: 10.3389/fpls.2023.1229495
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of soybean (Glycine max [L.] Merr.) germplasm for dissecting the quantitative trait nucleotides and candidate genes underlying yield-related traits

Abstract: Soybean (Glycine max [L.] Merr.) is one of the most significant crops in the world in terms of oil and protein. Owing to the rising demand for soybean products, there is an increasing need for improved varieties for more productive farming. However, complex correlation patterns among quantitative traits along with genetic interactions pose a challenge for soybean breeding. Association studies play an important role in the identification of accession with useful alleles by locating genomic sites associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 157 publications
0
0
0
Order By: Relevance
“…Among them, Glyma.09G102300 mainly encodes F-box related protein and F-box proteins are a family of proteins that exist widely in eukaryotes and contain the F-box domain. It plays an important role in cell cycle regulation, transcription regulation, apoptosis, cell signal transduction, growth and development [39,40]. In addition, studies have shown that F-box proteins OsFBX206, OsFBK12 can regulate the synthesis of ethylene and boisterousness for improving the grain size and yield in rice [41][42][43] .Besides, we found that NADH dehydrogenase1 alpha sub-complex was predicted to be an interacting protein of the fresh pod weight candidate gene Glyma.09G102300.…”
Section: Discussionmentioning
confidence: 88%
“…Among them, Glyma.09G102300 mainly encodes F-box related protein and F-box proteins are a family of proteins that exist widely in eukaryotes and contain the F-box domain. It plays an important role in cell cycle regulation, transcription regulation, apoptosis, cell signal transduction, growth and development [39,40]. In addition, studies have shown that F-box proteins OsFBX206, OsFBK12 can regulate the synthesis of ethylene and boisterousness for improving the grain size and yield in rice [41][42][43] .Besides, we found that NADH dehydrogenase1 alpha sub-complex was predicted to be an interacting protein of the fresh pod weight candidate gene Glyma.09G102300.…”
Section: Discussionmentioning
confidence: 88%
“…Functional characterization of these genes using transgenic approaches or gene editing technologies offers opportunities for targeted manipulation of yield-related traits in crops. Overall, the identification of yield-related genes and QTLs through genomic approaches provides a foundation for targeted breeding efforts aimed at enhancing crop productivity and resilience [39].…”
Section: Identification Of Yield-related Genes and Qtlsmentioning
confidence: 99%